2022
DOI: 10.3389/fcvm.2022.899050
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Increases In-Hospital Mortality of Acute Type A Aortic Dissection Patients Undergoing Open Surgical Repair: A Retrospective Study in the Chinese Population

Abstract: ObjectiveThe prevalence of obesity is increasing worldwide, and the role of the obesity paradox in cardiovascular surgery remains controversial. In this study, we redefined obesity according to the Chinese criteria and examined the relationship between obesity and in-hospital mortality in patients with acute type A aortic dissection (AAD) undergoing open surgical repair.Materials and MethodsA total of 289 patients with AAD (between 2014 and 2016) were divided into the non-obese group and obese group for correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The effect of BMI on perioperative mortality of ATAAD was extracted from 12 studies which included 5,522 patients. Single-center studies in China observed that mean BMI was associated with perioperative mortality of ATAAD, including 30-days mortality [ 21 ] (HR = 1.13, 95% CI: 1.03–1.25), in-hospital mortality [ 19 , 20 , 23 , 25 ] (OR = 1.15, 95% CI: 1.03–1.29, OR = 1.32, 95% CI: 1.03–1.70, HR = 2.61, 95% CI: 1.30–5.22 and OR = 1.09, 95% CI: 1.04–1.15). Consistently, different perioperative mortality of ATAAD was found between different BMI categories.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of BMI on perioperative mortality of ATAAD was extracted from 12 studies which included 5,522 patients. Single-center studies in China observed that mean BMI was associated with perioperative mortality of ATAAD, including 30-days mortality [ 21 ] (HR = 1.13, 95% CI: 1.03–1.25), in-hospital mortality [ 19 , 20 , 23 , 25 ] (OR = 1.15, 95% CI: 1.03–1.29, OR = 1.32, 95% CI: 1.03–1.70, HR = 2.61, 95% CI: 1.30–5.22 and OR = 1.09, 95% CI: 1.04–1.15). Consistently, different perioperative mortality of ATAAD was found between different BMI categories.…”
Section: Resultsmentioning
confidence: 99%
“…The Obese group manifested a significantly elevated rate of preoperative hypoxemia (74.0%), a statistic surpassing that of its counterparts. This can be rooted in the physiopathological modifications synonymous with obesity, such as reduced pulmonary volume and augmented respiratory effort ( 14 ). To address this, we propose preoperative optimization strategies for respiratory function, including preoperative pulmonary rehabilitation or noninvasive ventilation support, particularly for obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lio et al reported a higher perioperative mortality rate and reduced 5-year survival rates in obese patients with emergency surgery for ATAAD [43]. Xiaogao et al found that although obesity was more common in younger patients, it was more likely to cause death in elderly patients (age > 60 years) [13]. The high rate of mortality could be explained by the increased risk of low cardiac output syndrome and pulmonary complications in obese patients [43].…”
Section: Risk Factor or 95% CI Pmentioning
confidence: 99%
“…Patients with obesity are more predis posed to developing ATAAD [12]. Moreover, obese patients with emergency surgery fo ATAAD had higher operative mortality and an increased risk of low cardiac output syn drome and pulmonary complications [12,13].…”
Section: Introductionmentioning
confidence: 99%